When facilitation meets clonal integration in forest canopies. Issue 1 (25th October 2019) - Lu, Hua‐Zheng; Brooker, Rob; Song, Liang; Liu, Wen‐Yao; Sack, Lawren; Zhang, Jiao‐Lin; Yu, Fei‐Hai
Summary: Few studies have explored how – within the same system – clonality and positive plant–plant interactions might interact to regulate plant community composition. Canopy‐dwelling epiphytes in species‐rich forests provide an ideal system for studying this because many epiphytic vascular plants undertake clonal growth and because vascular epiphytes colonize canopy habitats after the formation of nonvascular epiphyte (i.e. bryophyte and lichen) mats. We investigated how clonal integration of seven dominant vascular epiphytes influenced inter‐specific interactions between vascular epiphytes and nonvascular epiphytes in a subtropical montane moist forest in southwest China. Both clonal integration and environmental buffering from nonvascular epiphytes increased survival and growth of vascular epiphytes. The benefits of clonal integration for vascular epiphytes were higher when nonvascular epiphytes were removed. Similarly, facilitation from nonvascular epiphytes played a more important role when clonal integration of vascular epiphytes was eliminated. Overall, clonal integration had greater benefits than inter‐specific facilitation. This study provides novel evidence for interactive effects of clonality and facilitation between vascular and nonvascular species, and has implications for our understanding of a wide range of ecosystems where both high levels of clonality and facilitation are expected to occur.